Review of Paul A. Roth’s The Philosophical Structure of Historical Explanation (Book review) - Virmajoki Veli (Cambridge University Press, 2025)
Roth’s book is rich and intense. In a relatively short space, it seeks to locate historical explanations within our general metaphysical and epistemic predicaments. Understanding the argumentative nuances of the book requires knowledge of analytic philosophy of history, analytic philosophy in general, philosophy and history of science, and narrative theory. As Roth’s book provides an excellent overview of the potential richness and importance of philosophy of history, critically engaging with its contents and strategy enables us to see possible ways to cross-fertilize current philosophy of history and trends in other areas of philosophical research. In this review, I focus on those issues that might interest philosophers of science the most.